Implementing English for Specific Purposes (ESP) in the Sharia Economics Study Program: Preparing Graduates for Diverse Professional Careers - Tira Nur Fitria (Jurnal Ilmiah Ekonomi Islam, 2026)
The study describes the implementation of English for Specific Purposes (ESP) in the Sharia Economics Study Program in preparing graduates to meet the demands of diverse professional careers in the field of Sharia/Islamic economics and related fields. This study uses a descriptive qualitative research method. This study involved undergraduate students from various semesters to obtain detailed insights into how ESP supports their professional career preparation. The findings indicate that the implementation of English for Specific Purposes (ESP) in the Sharia Economics Study Program plays a crucial role in preparing students for professional contexts within Sharia-based economic sectors. Designed through needs analysis that considered students’ academic backgrounds, career aspirations, and workplace communication demands, the ESP course emphasized English as a practical professional tool rather than merely a general language skill. Instruction integrated all language skills with discipline-specific content, authentic materials, and real workplace scenarios related to Islamic banking, Sharia financial institutions, halal industries, and entrepreneurship. As a result, students demonstrated significant improvement in specialized vocabulary mastery, professional and functional communication skills, and confidence in using English for presentations, discussions, and professional writing. The course also incorporated authentic learning resources and embedded Islamic values, Sharia principles, and professional ethics, supporting not only linguistic competence but also character development and ethical awareness. Furthermore, ESP prepared students for diverse career paths by developing transferable communication skills applicable across multiple professional roles in the Sharia economic sector, thereby enhancing employability readiness and professional identity. However, several challenges were identified, including varied student proficiency levels, limited prior exposure to discipline-specific English, time constraints, scarcity of specialized teaching materials, and institutional limitations affecting curriculum alignment. These findings suggest important implications for ESP curriculum development, highlighting the need for systematic needs-based design, integration of language and content, collaboration between English and subject-matter lecturers, development of tailored materials, performance-based assessments, and sustained institutional support to ensure that ESP remains relevant to evolving industry demands and effectively bridges academic learning with professional workplace expectations. It is suggested that ESP implementation in Sharia Economics programs be strengthened through systematic, needs-based curriculum design and closer collaboration between English lecturers and subject experts. Institutions should support the development of specialized materials, adequate instructional time, and interdisciplinary coordination. Lecturers should also apply differentiated and confidence-building strategies to address varied student proficiency levels. In addition, ESP should continue to integrate authentic workplace tasks, performance-based assessments, and Islamic values to ensure relevance to professional demands. Continuous evaluation is necessary to keep the ESP curriculum responsive to evolving industry needs and to enhance students’ employability readiness.